Tax Risk Dynamics and Tax Planning Activity Nexus: Evidence From Banks in Ghana (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study investigates the tax risk tax planning nexus of banks in Ghana. The paper explores the multidimensionality of tax risk and its consequences for tax planning activity.Design/Methodology/Approach: Due to data availability and completeness, the study used a purposive sampling technique to sample 20 banks. The study focused on the universal banks in Ghana, with data from 2008 to 2022 generated from the audited financial statements, interpolated into monthly frequencies, and analysed using the Generalised Method of Moment to test the nexus.Research Limitation: Although the findings presented in this study are grounded in the Ghanaian context, their implications extend beyond the Ghanaian setting. Also, while there are other equally important branches of the financial sector, the study only concentrated on the banking sector.Findings: The findings show that differential/avoidance tax risk and rolling tax risk significantly positively affect the cash-effective tax rate. Therefore, it is concluded that a high tax risk reduces banks' aggressive tax planning activities in Ghana.Practical Implication: A perceived high tax risk could lead to a high tax-paying culture. The tax authority should enforce regulatory sanctions to elicit high corporate tax compliance and improve this culture.Social Implication: A high tax risk could result in increased tax revenue obligations, improving tax revenues for providing essential services like employment, education, healthcare, and infrastructure.Originality/ Value: The study is one of the foundational studies in the Ghanaian setting to explore tax risk dynamics as antecedents of tax planning activity. By extending the empirical analyses to the banking sector, the study has not only recognised the heterogeneous characteristics of tax but also provides a unique understanding of the relationship from the banking sector where empirical evidence is virtually absent.
Keywords: Bank. rolling tax risk. tax planning. tax rate. tax risk